2014
DOI: 10.1007/s10557-014-6543-8
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine Non- Versus Re-Circulation During Isolated Heart Perfusion - A Jekyll and Hyde Effect?

Abstract: Aims In isolated rat heart perfusion experiments, drug administration occurs via retrograde perfusion. This can be done in the non-recirculating mode (coronary effluent is discarded), or recirculating mode (coronary effluent is collected and reused). It was recently observed in our lab whi le using sanguinarine, an MKP-1 inhibitor, that there were differences in outcomes depending on the mode of recirculation used. Methods and ResultsHearts from control (C); diet-induced obese (DIO) Wis tar rats and their age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…Further, previous studies have extensively demonstrated that AMPK stimulation can improve health in different contexts. The AMPK signaling pathway provides an alternative to the insulin-dependent glucose uptake pathway in muscle by activating phosphatidyl-inositol-3 kinase (PI3-K) and PKB/Akt [ 253 ]. Data support that AMPK inhibits Rab-GTPase activating proteins AS160 (TBC1D4) and TBC1D1, which triggers Glut-4 trafficking to the plasma membrane [ 274 ].…”
Section: A Plant-based Diet and Metabolic Syndromementioning
confidence: 99%
“…Further, previous studies have extensively demonstrated that AMPK stimulation can improve health in different contexts. The AMPK signaling pathway provides an alternative to the insulin-dependent glucose uptake pathway in muscle by activating phosphatidyl-inositol-3 kinase (PI3-K) and PKB/Akt [ 253 ]. Data support that AMPK inhibits Rab-GTPase activating proteins AS160 (TBC1D4) and TBC1D1, which triggers Glut-4 trafficking to the plasma membrane [ 274 ].…”
Section: A Plant-based Diet and Metabolic Syndromementioning
confidence: 99%
“…To verify the sensitivity of the method, new experiments were performed using the GLUT4 translocation activators ionomycin (Ca 2+ ionophore) [ 31 , 32 ] and AICAR (AMPK activator) [ 17 , 33 ], and the widely used PI3K inhibitor wortmannin to prevent GLUT4 translocation by insulin [ 33 , 34 ]. Figure 3 shows that FC was able to detect the increase in GLUT4myc at the plasma membrane by ionomycin and AICAR.…”
Section: Resultsmentioning
confidence: 99%
“…Another hypoxia/metabolic sensor is adenosine monophosphate-activated protein kinase (AMPK), which responds primarily to the prevailing AMP:ATP ratio but also to the intracellular calcium concentration via calcium calmodulin kinase kinase 2 (CaMKK2) [ 48 ]. There is cross -talk between AMPK and HIF-1 pathways that promote gene transcription of glucose transport via glucose transporters (GLUT) [ 49 ] and sodium-glucose -linked transporter 1 (SGLT1) [ 50 ], both of which are beneficial as the myocardium switches towards glucose metabolism. Such changes would be highly beneficial in the border zone of the ischemic myocardium, where hypoxia likely persists rather than progressing through to necrosis as found towards the center of the ischemic zone.…”
Section: Cardioprotection – Attenuation Of Myocardial Ischemia/reperf...mentioning
confidence: 99%